An Overview of Agricultural Pollution in the Philippines : The Livestock Sector 2016 - World Bank (World Bank, Washington, DC, 2018)
This report is part of a national overview of agricultural pollution in the Philippines, commissioned by the World Bank. The overview consists of three ‘chapters’ on the crops, livestock, and fisheries sub-sectors, and a summary report. This ‘chapter’ provides a broad national overview of: (a) the magnitude, impacts, and drivers of pollution related to the livestock sector’s development; (b) measures that have been taken by the public sector to manage or mitigate this pollution; and (c) existing knowledge gaps and directions for future research. This report was prepared based on existing literature, recent analyses, national and international statistics, and interviews. It did not involve new primary research and did not attempt to cover pollution issues that arise in the broader livestock value chain, outside the farmgate, for instance from slaughterhouses, feed processing plants, or veterinary drug factories.